(untitled) (Baghdad Science Journal, 2022)
Biodiesel production from microalgae depends on the biomass and lipid production. Both biomass and lipid accumulation is controlled by several factors. The effect of various culture media (BG11, BBM, and Urea), nutrients stress [nitrogen (N), phosphorous (P), magnesium (Mg) and carbonate (CO3)] and gamma (γ) radiation on the growth and lipid accumulation of Dictyochloropsis splendida were investigated. The highest biomass and lipid yield of D. splendida were achieved on BG11 medium. Cultivation of D. splendida in a medium containing 3000 mg L−1 N, or 160 mg L−1 P, or 113 mg L−1 Mg, or 20 mg L-1 CO3, led to enhanced growth rate. While under the low concentrations of nutrients caused a marked increase in the lipid content. Cultures exposure to 25 Gy of γ-rays, led to an increase in lipid content up to 18.26 ± 0.81 %. Lipid profile showed the maximum presence of saturated fatty acids (SFAs, 63.33%), and unsaturated fatty acids (UFAs, 37.02%). Fatty acids (FAs) recorded the predominance of C16:0, C18:2, C15:0 and C16:1, which strongly proved D. splendida is a promising feedstock for biodiesel production.